IMPLEMENTATION OF THE BLENDED LEARNING MODEL IN IMPROVING LEARNING OUTCOMES IN THE COGNITIVE DOMAIN - Atika, Yova; Sari, Dewi Purnama; Warsah, Idi (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
This research aims to improve student learning outcomes in Islamic Religious Education subjects at SMA Negeri 1 Rejang Lebong through the application of the blended learning model. The type of research used in this research is classroom action research (PTK). The subjects of this research were 32 students in class XI A of SMA Negeri 1 Rejang Lebong. The data collection techniques used in this research are: tests, observation and documentation. The research data obtained was analyzed descriptively using simple descriptive statistics. Based on the findings that learning Islamic Religious Education using the blended learning model can improve student learning outcomes in the cognitive domain from cycle 1 before the blended learning model is implemented by 77.97% and in cycle II after the blended learning model is implemented it increases to 92.5%.